Prevention of Neural Tube Defects in Europe: A Public Health Failure - Morris, Joan K.; Addor, Marie-Claude; Ballardini, Elisa; Barisic, Ingeborg; Barrachina-Bonet, Laia; Braz, Paula; Cavero-Carbonell, Clara; Den Hond, Elly; Garne, Ester; Gatt, Miriam; Haeusler, Martin; Khoshnood, Babak; et al. (Frontiers in Pediatrics, 2021)
Objective: Thirty years ago it was demonstrated that folic acid taken before pregnancy and in early pregnancy reduced the risk of a neural tube defect (NTD). Despite Public Health Initiatives across Europe recommending that women take 0.4 mg folic acid before becoming pregnant and during the first trimester, the prevalence of NTD pregnancies has not materially decreased in the EU since 1998, in contrast to the dramatic fall observed in the USA. This study aimed to estimate the number of NTD pregnancies that would have been prevented if flour had been fortified with folic acid in Europe from 1998 as it had been in the USA. Design and Setting: The number of NTD pregnancies from 1998 to 2017 that would have been prevented if folic acid fortification had been implemented in the 28 countries who were members of the European Union in 2019 was predicted was predicted using data on NTD prevalence from 35 EUROCAT congenital anomaly registries and literature searches for population serum folate levels and folic acid supplementation. Results: From 1998 to 2017 an estimated 95,213 NTD pregnancies occurred amongst 104 million births in the 28 countries in the EU, a prevalence of 0.92 per 1,000 births. The median serum folate level in Europe over this time period was estimated to be 14.1 μg/L. There is a lack of information about women taking folic acid supplements before becoming pregnant and during the first trimester of pregnancy, with one meta-analysis indicating that around 25% of women did so. An estimated 14,600 NTD pregnancies may have been prevented if the European countries had implemented fortification at the level adopted by the USA in 1998 and 25% of women took folic acid supplements. An estimated 19,500 NTD pregnancies would have been prevented if no women took folic acid supplements. Conclusions: This study suggests that failure to implement mandatory folic acid fortification in the 28 European countries has caused, and continues to cause, neural tube defects to occur in almost 1,000 pregnancies every year.